Electroacupuncture promotes nerve regeneration and functional recovery in rats with spinal cord contusion through the coordinate interaction of CD4 and BDNF. Issue 3 (26th July 2022) - Zhang, Bao‐Lei; Guo, Xi‐Liang
Abstract: To explore the effect of electroacupuncture on spinal cord injury (SCI) involving immune‐related factors and regeneration‐related factors in rats. The model of spinal cord contusion was established by PCI 3000 instrument. Two types of acupuncture points were selected for electroacupuncture treatment on rats. The rats were tested once a week, and the fiber remodeling was detected by magnetic resonance imaging. Transcriptome sequencing was performed on spinal scar samples. Using Python to write code, statistical analysis and bioinformatics analysis of the correlation between transcriptome sequencing data and fiber reconstruction results are carried out. Lastly, the expression of CD4 and brain‐derived neurotrophic factor (BDNF) in spinal cord scar was verified by quantitative reverse‐transcription polymerase chain reaction (qRT‐PCR). Electroacupuncture exhibited a positive effect on the recovery of motor function in rats after SCI. Bioinformatics analysis found a direct interaction between CD4 and BDNF. Transcriptome sequencing and PCR results verified that electroacupuncture significantly reduced the expression of CD4, and increased significantly the expression of BDNF, simultaneously corresponding to nerve regeneration in rats with SCI. Our results showed that electroacupuncture intervention in SCI rats improves neural behavior via inhibiting the expression of CD4 and increasing the expression of BDNF. Abstract : Flow chart of the study. At present, the nerve regeneration repair and treatment for spinal cord injury (SCI) patients is still in an exploratory stage, and EA has received much attention as a representative treatment for traditional Chinese medicine (TCM), but its molecular mechanism of action on functional recovery and nerve repair of SCI has not been fully elucidated. We established an SD rat spinal cord contusion (SCC) model, treated with electroacupuncture for 7 weeks, and performed Basso‐Beattie‐Bresnahan (BBB) score every Sunday. Rats were subsequently subjected to MRI, fiber reconstruction, and transcriptome sequencing of spinal scar samples. Using Python to write code, statistical analysis and bioinformatics analysis of the correlation between transcriptome sequencing data and fiber reconstruction results are carried out. Lastly, the expression of CD4 and brain‐derived neurotrophic factor (BDNF) in spinal cord scar was verified by quantitative reverse‐transcription polymerase chain reaction (qRT‐PCR). RatsThe correlation analysis of transcriptome sequencing results with the number of reconstructed spinal cord fiber bundles revealed that the changes in expression of inflammatory factors represented by CD4 showed a strong negative correlation with the number of fibers, and the bioinformatics prediction revealed that there was a direct interaction between CD4 and a series of molecules of neural regeneration represented by brain‐derived neurotrophic factor (BDNF). Therefore, it is inferred that the electroacupuncture treatment in spinal cord‐injured rats may promote the regeneration of spinal cord fibers and recovery of motor function by reducing the inhibition of CD4 expression and thus enhancing the expression of BDNF.